USE OF PARTIAL LEAST SQUARES STRUCTURAL EQUATION MODELLING TO IDENTIFY CRITICAL SUCCESS FACTORS IN 6 SIGMA IMPLEMENTATION - García Martínez, Rafael; Noriega, Salvador; Torres, Vianey; Poblano Ojinaga, Eduardo Rafael; Álvarez Argüelles, Mariela (2024)
https://www.revistadyna.com/search/use-of-partial-least-squares-structural-equation-modelling-to-identify-critical-success-factors-in-6